As palavras são vida? Um estudo sobre a utilização da linguagem poética e informal no ensino da medicina - DUARTE, Tiago Braga (2023)
INTRODUCTION: In the whole medical philosofer’s academy, the student is faced with numerous comparative, informal and poetic terms, and the use of metaphors is very recurrent in medical education throughout the curriculum. OBJECTIVE: The present study aimed to do a formal record of these medical terms. METHODOLOGY: The terms were collected through direct consultation of the medical literature, covering four major medical areas, in addition to two other specialties. RESULTS: In the universe of 865 terms, Internal Medicine corresponded to 35.8% of this total. Clinical Pathology contributed with 26.2%, followed by Pediatrics (22.0%), General Surgery (17.4%), Radiology (10.5%), and Gynecology and Obstetrics, in turn, (7.0%). 667 terms (77.5%) referred only to images while 168 (19.5%) terms referred to the meaning. In addition, only 92 (10.6%) of the terms appear in the international database consulted, while 773 (89.4%) do not exist. CONCLUSION: Medicine, once creating informal terms for its learning and teaching, is also a human science. In these informal and poetic terms, it was seen that the image allusions were the majority. However, there is a need to be a greater appreciation of these expressions at a scientific level, with updates to the DeCS database so more of these terms and expressions can be included. Moreover, it is important that further studies in this rich in possibilities and still underexplored area are made.